Impact of Thyme Microcapsules on Histamine Production by Proteus bacillus in Xinjiang Smoked Horsemeat Sausage - Honghong Yu; Yali Huang; Liliang Lu; Yuhan Liu; Zonggui Tang; Shiling Lu (Foods, 2021)
Here, we explored the influences of thyme microcapsules on the growth, gene expression, and histamine accumulation by Proteus bacillus isolated from smoked horsemeat sausage. RT-qPCR was employed to evaluate the gene expression level of histidine decarboxylase (HDC) cascade-associated genes. We used HPLC to monitor histamine concentration both in pure culture as well as in the processing of smoked horsemeat sausage. Results showed that histamine accumulation was suppressed by thyme microcapsule inhibitory effect on the histamine-producing bacteria and the reduction in the transcription of hdcA and hdcP genes. Besides, compared with thyme essential oil (EO), thyme microcapsules exhibited higher antibacterial activity and had a higher score for overall acceptance. Therefore, the addition of thyme microcapsules in Xinjiang smoked horsemeat sausage inhibits histamine accumulation.